A critical review on exploitation of agro-industrial biomass as substrates for the therapeutic microbial enzymes production and implemented protein purification techniques. (May 2022) - Raina, Diksha; Kumar, Vinod; Saran, Saurabh
Abstract: Annually, a huge amount of waste is generated by the industries that use agricultural biomass. Researchers have looked into employing this cheap and renewable agro-biomass as a substrate for enzyme production via fermentation processes to meet the ever-increasing worldwide need. Although there are a number of sources for enzyme extraction, microbial sources have dominated industrial sectors due to their easy availability and rapid growth. Microbial enzymes are currently used in a variety of industries, including pharmaceuticals, food, biofuels, textiles, paper, detergents, and so on, and using these nutritious feedstocks not only reduces production costs but also helps to reduce environmental concerns. The present review focuses on the therapeutic microbial enzymes produced using different agro-industrial biomass as raw materials, with down-streaming techniques for obtaining a final pure product. Additionally, the article also discussed biomass pretreatment processes, including physical, chemical and biological. The type of pretreatment method to be used is mostly governed by the intended use of the major molecular components of biomass (cellulose, hemicelluloses and lignin). Finally, purification challenges are included. All of this information will be useful in the industrial synthesis of high-purity targeted enzymes if the crucial aspects that have been discussed are taken into account. Graphical abstract: Image 1 Highlights: Production of microbial origin enzymes using different fermentation technologies. Agro-industrial wastes are best as substrates for obtaining maximum enzyme yields. Down-streaming strategies are critical for enzyme usage as therapeutic agents.